2021
DOI: 10.31234/osf.io/tg7xr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do Attitudes, Trust, and Acceptance of Pseudoscience and Conspiracy Theories Predict COVID-19 Vaccination Status?

Abstract: Vaccine hesitancy among the general population has become a primary concern for contending with the COVID pandemic as policymakers continue to exhaust options to incentivize individuals and vaccination uptake begins stagnating. The current study explores the relative contributions of several potential predictors of vaccine hesitancy. In an online cross-sectional survey study, 917 individuals from the U.S. were assessed on general and COVID-specific vaccine attitudes, COVID conspiracy and pseudoscientific belie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Vaccination is regarded as a powerful tool in the fight against pandemics, both to alleviate the burden on hospitals and health workers and to reduce fatalities. However, the public reactions to COVID-19 vaccines have varied from strong demand to 'anti-vax' behaviors (Benoit and Mauldin, 2021), with different responses reflecting differing levels of trust in governments and science at both the individual and societal levels (Debus and Tosun, 2021;Grawitch and Lavigne, 2021). Jelnov and Jelnov (2022) showed that government accountability contributes to the success of vaccination campaigns, with higher vaccination rates observed in more liberal and less corrupt countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vaccination is regarded as a powerful tool in the fight against pandemics, both to alleviate the burden on hospitals and health workers and to reduce fatalities. However, the public reactions to COVID-19 vaccines have varied from strong demand to 'anti-vax' behaviors (Benoit and Mauldin, 2021), with different responses reflecting differing levels of trust in governments and science at both the individual and societal levels (Debus and Tosun, 2021;Grawitch and Lavigne, 2021). Jelnov and Jelnov (2022) showed that government accountability contributes to the success of vaccination campaigns, with higher vaccination rates observed in more liberal and less corrupt countries.…”
Section: Literature Reviewmentioning
confidence: 99%